"It was amazing to see our projects come to life!" Developing affective learning during geography fieldwork through tropophilia. Issue 2 (3rd April 2017) - Holton, Mark
Abstract: This research, conducted with groups of undergraduate students before and after a European fieldwork exercise, critically examines the pedagogic value of fieldwork and its ability to provide students with transferable skills. This is achieved using Anderson and Erskine's lens of tropophilia – the aesthetic connection between people and place – to explore the influence of "being" in the field upon affective learning. In doing so, this research suggests (1) that encouraging students to recognize how their own affective skills may influence the types of knowledge(s) that are produced on fieldtrips and (2) that people-place connections have the ability to inspire students to become more self-reflexive about their position(s) as learners.